The Effect of Self Talk Strategy in Public Speaking as EFL Classroom on the Third Year Students (Academic Year 2013) at English Department in FKIP Universitas HKBP Nommensen Pematangsiantar - Rudiarman Purba; Sotarduga Sihombing (Journal of English Language and Culture, 2018)
This research will tend to find out the significance and the effect Self Talk Strategy in Public Speaking as EFL classroom on the third year students (Academic Year 2013) at English Department in FKIP Universitas HKBP Nommensen Pematangsiantar. This research will use experimental research design. To answer the problems of the research, the writer uses the following theories: O’Malley, et al. (2002), Braiker (1987), Vygotsky (1986), Winsler et al (2009), Gaskins (2005) in self-talk strategy and the writer uses the theory of Harris (1969), Ur (1996), Harmer (1998), Scrinever (2005), Thornburry (2005), Grugeon et al (2005) and Harmer (2007). The population of this research is the third year students (Academic Year 2013) at English Department that sit in Public Speaking Class  in FKIP Universitas HKBP Nommensen Pematangsiantar. There are 40 students taken as the sample of this research. The sample was divided into two groups: the first group (20 students) as the experimental group and the second group (20 students) as the control group. The writers will give a treatment in class by applying self talk strategy in teaching speaking in public speaking class. To analyze the data, the writer uses the theory of Arikunto. After analyzing and calculating the data, the writer finds that The Mean Score was 7.8 and the value of t-test was higher than t-table (t-test > t-table), 2.671 > 1.686. Ha (Alternate Hypothesis) was accepted and Ho (Null Hypothesis) was rejected. Keywords:  Self Talk Strategy, Speaking, English, Foreign Language, Teaching